Application of modified SWIM technique in mechanical thrombectomy of acute ischemic stroke - CUI Jie⁃men; YE Bin; GONG Xin; ZHANG Hong⁃yan; SUN Xuan (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate the efficacy and safety of modified SWIM technique for mechanical thrombectomy in patients with acute ischemic stroke. Methods Total 114 patients with acute ischemic stroke who underwent mechanical thrombectomy in The Third the People's Hospital of Bengbu from January 2021 to January 2024 were included. Modified SWIM technique (modified thrombectomy group, n = 57) and conventional SWIM technique (conventional thrombectomy group, n = 57) were given respectively. Vascular recanalization rate of the first thrombectomy, overall vascular recanalization rate, the number of thrombectomy, puncture⁃to⁃reperfusion time, near⁃term neurological deficits [National Institutes of Health Stroke Scale (NIHSS) at 14 d postoperatively] and long⁃term neurological prognosis [modified Rankin Scale (mRS) at 90 d postoperatively] were recorded, as well as symptomatic intracranial hemorrhage (sICH) rate and mortality. Results The vascular recanalization rate of the first thrombectomy in modified thrombectomy group was higher than that in conventional thrombectomy group (χ2 = 5.054, P = 0.025), the number of thrombectomy was less than (Z = 2.014, P = 0.044), and puncture⁃to⁃reperfusion time was shorter than (Z = 2.630, P = 0.009) conventional thrombectomy group. There was a statistically significant difference in NIHSS score between modified thrombectomy group and conventional thrombectomy group before and after surgery (F = 5.185, P = 0.025), and there was also a statistically significant difference in NIHSS score between the 2 groups at admission and 14 d after surgery (F = 133.705, P = 0.000). There was not an interaction between treatment factors and measurement times (F = 3.148, P = 0.079). The NIHSS score 14 d after surgery in modified thrombectomy group was lower than that in conventional thrombectomy group (t =2.969, P = 0.004). The NIHSS score of modified thrombectomy group (t = 10.286, P = 0.000) and conventional thrombectomy group (t = 6.428, P = 0.000) were lower at 14 d after surgery than those at admission. There was a statistically significant difference in mRS score between modified thrombectomy group and conventional thrombectomy group before and after surgery (F = 7.581, P = 0.007), and there was also a statistically significant difference in mRS score between the 2 groups at admission and 90 d after surgery (F = 277.328, P = 0.000). There was an interaction between treatment factors and measurement times (F = 10.471, P = 0.002), and the effect of modified SWIM technique was better. Modified thrombectomy group had a better prognosis (mRS score ≤ 2) at 90 d after surgery than conventional thrombectomy group (χ2 = 4.267, P = 0.039). There were no significant differences in the incidence of postoperative sICH rate (χ2 = 0.077, P = 0.782) and the mortality (χ2 = 0.101, P = 0.751) between 2 groups. Conclusions The application of modified SWIM technique in mechanical thrombectomy has better efficacy and safety than conventional SWIM technique, and is worthy of clinical promotion.